Edukasi Penerapan Sistem 3R (Reduce, Reuse, Recycle) pada Masyarakat Kota Batam - Sumantika, Arsyad; Sirait, Ganda; Prasetyo, Bahariandi Aji; Tarigan, Elsya P.L. (Jurnal Pengabdian Cendikia Nusantara, 2025)
The focus of this community service initiative is to provide an understanding to the community about the implementation of the 3R system (Reduce, Reuse, Recycle) as an effective waste management approach in Batam City. The background of this activity is the increase in the volume of household waste and the decreasing public knowledge about sustainable waste management. The application of the method uses a persuasive strategy to increase public awareness of the importance of protecting the environment and converting waste into economic value. To achieve this goal, materials about waste, information about the dangers of waste, and the application of the 3R method in household waste management are provided. The community service team also distributed books on how to maintain a clean and healthy environment and manage waste. The results of the activity showed an increase in public understanding of the 3R method and high enthusiasm for improving waste management in the future. This activity not only aims to provide knowledge about processing waste into something valuable, but also encourages the growth of entrepreneurial ideas related to waste management in Batam City.